Hypericum scruglii Bacchetta, Brullo & Salmeri, is it a possible natural resource against Fibromyalgia? - Mauro Giovanni Carta; Maria Manconi; Gianluigi Bacchetta; Germano Orru; Maria Cristina Deiddda; Mario Musu; Gabriele Finco (International Journal of Phytomedicine, 2020)
Fibromyalgia (FM) is today a serious public health issue. Tested treatments have shown limited efficacy. Oxidative stress probably interacting with the glutamatergic / gamma -Aminobutyric acid balance may play a role. Antidepressants improve sleep and mood especially those with double action on serotonin and norepinephrine, but these are also those with a greater risk of manic switch considering the high frequency of comorbidity with bipolar disorders. This narrative review tries to evaluate, on the basis of in vitro and animal studies, the potential utility in fibromyalgia of Hypericum Scruglii, an endemic species peculiar to the island of Sardinia. The studies that have verified the antidepressant efficacy of Hypericum Perforatum and the first attempts of its use in fibromyalgia are reported as well as the studies that found the phloroglucinol derivatives from Hypericum longistylum (well-known in traditional Chinese medicine) that facilitate the differentiation of neural progenitor cells, and increase the efficiency of differentiation into serotonergic neurons. The advantage of Hypericum Scruglii may be represented by the anti-oxidant potential revealed to be greater than in other species of the same genus. The paper also describes new approaches to improving the oral bioavailability of very poor water-soluble molecules of hypericum extracts.